School Management System: A Web and Mobile-Based Platform for Prefect of Discipline at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A school management system is a platform designed for organizing and managing theactivities of an institution. As it also helps to manage the student’s information through anonline platform. The development of a Web and Mobile-Based Platform for the Prefect ofDiscipline was conducted for online monitoring and for online management of the student'sand faculty members' records regarding their violations. Corresponding to that are thedisciplinary actions, including the status of their cases. As well, the records will become moreorganized, secure, and accurate. The list of violations and accompanying disciplinaryprocedures will be based on the students' handbook. The system also generates anappointment for the students and teachers using the web and mobile-based platforms.In dealing with the issue that the project team ran into, the developer team developed asystem based on the client’s requirements. The project system contains a login for security sothat only authorized people will access the system, a dashboard to organize the report andeasily view the summary report through the charts, services for receiving complaints, anappointment for creating the scheduled appointment, real-time data reports, and recordscontaining all the records and the status of each case.This project study will help future researchers by giving them the needed information. Thestudy discusses the new system’s features. The Web and Mobile-based platform for Prefect ofDiscipline will improve the transaction from a paper-based to an online platform. In that way, itwill secure the information and data from unofficial users, enable the user to complain online,allow viewing of the appointment that is also scheduled online, reduce the time to find theuser’s record, and lastly, show it in real-time.
Keywords: IT & Management